Negative Photoconductive Effects in Uncooled InAs Nanowire Photodetectors - yiyun, zhang; Zhang, Yiyun; Pan, Dong; Xiaoyan, Yi; Jianhua, Zhao; Jinmin, Li (Frontiers in Physics, 2021)
One-dimensional, direct, and narrow band gap indium-arsenic (InAs) nanowires (NWs) have been emerging with great potentials for the next generation wide-spectrum photodetectors. In this study, metal-semiconductor-metal (MSM) structure InAs NW-based photodetectors were fabricated by transferring MBE-grown NWs onto a sapphire substrate via a mechanical stamping method. These NW detectors exhibit strong negative photoconductive (NPC) effects, which is likely caused by the carrier dynamics in an incidence-dependent “core-shell” structure of the NWs. Specifically, under the irradiation of a 405 nm violet laser, the maximum Idark/Ilight ratio reaches 102 and the NPC gain reaches 105 at a low bias voltage of 0.2 V. At room temperature, the rise and decay times of InAs-NW devices are 0.005 s and 2.645 s respectively. These InAs NW devices with high Idark/Ilight ratio and NPC gain can be potentially used in the field of vis/near-IR light communication in the future.